2023
DOI: 10.3390/cancers15133414
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Biosensing Methods to Monitor Lung Cancer Biomarkers in Biological Samples: A Comprehensive Review

Raja Chinnappan,
Tanveer Ahmad Mir,
Sulaiman Alsalameh
et al.

Abstract: Lung cancer is the most commonly diagnosed of all cancers and one of the leading causes of cancer deaths among men and women worldwide, causing 1.5 million deaths every year. Despite developments in cancer treatment technologies and new pharmaceutical products, high mortality and morbidity remain major challenges for researchers. More than 75% of lung cancer patients are diagnosed in advanced stages, leading to poor prognosis. Lung cancer is a multistep process associated with genetic and epigenetic abnormalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 233 publications
(278 reference statements)
0
3
0
Order By: Relevance
“…In many circumstances, chemotherapy has little potential despite being the most widely used cancer therapy approach. oral or intravenous administration of drugs is the conventional method of chemotherapeutic medications so that only a portion of the dosage reaches the tumor site and the medication is distributed throughout the body [ 579 ] Approximately 1.5 million people worldwide lose their lives to lung cancer each year, making it the most frequently diagnosed cancer overall and one of the main causes of cancer-related fatalities in both men and women [ 580 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In many circumstances, chemotherapy has little potential despite being the most widely used cancer therapy approach. oral or intravenous administration of drugs is the conventional method of chemotherapeutic medications so that only a portion of the dosage reaches the tumor site and the medication is distributed throughout the body [ 579 ] Approximately 1.5 million people worldwide lose their lives to lung cancer each year, making it the most frequently diagnosed cancer overall and one of the main causes of cancer-related fatalities in both men and women [ 580 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Researchers have focused mainly on enhancing the limit of detection (LOD), time-dependent sensitivity, and selectivity of the target analyte. So, efforts are directed at improving the affinity of recognition surfaces to biomarkers, using advanced fabrication strategies, modifying surface chemicals, and incorporating nanomaterials [36][37][38][39].…”
Section: Overview Of Biosensing Technologymentioning
confidence: 99%
“…Therefore, there is great anticipation from researchers to develop simple, cheap, and easy-to-use point-of-care (POC) diagnostic tools to diagnose and monitor patients’ health status. Several research groups have reported strategies for POC diagnosis by detecting metabolites and proteins using paper, thread, and magnetic levitation [ 15 , 16 , 17 , 18 ]. In addition, inexpensive colorimetric enzyme-linked immunosorbent assays (ELISAs) using paper have also been developed to detect antibodies in biological fluids [ 19 ].…”
Section: Introductionmentioning
confidence: 99%